Programa de Formação Online de Mentores da UFSCar: contribuições para o desenvolvimento profissional de professores iniciantes participantes - Gobato, Paula Grizzo (Universidade Federal de São Carlos, 2020)
The main objective of this research is to analyze the mentoring actions that may have contributed to the possible professional development and teaching learning by the beginning teachers monitored in the Online Mentors Education Program. Specifically, it also seeks to answer the following research questions: Has the support of OMEP mentors assisted beginning teachers to overcome and/or minimize the early career difficulties recorded and diagnosed by mentors? If so, what were the difficulties overcome and/or minimized? What mentoring actions, developed by the mentors, contributed to the professional development of the beginning teachers from the perspective of the mentors? If no contributions have been identified, what are the reasons given? The theoretical references on which the present research was based take into account the characteristics and challenges of initial teacher training; the teacher's life cycle and its characteristics; training needs of beginning teachers; continuing teacher education for the beginning teacher; professional support programs for the beginning teacher; mentoring programs in Brazil; the knowledge base and the pedagogical reasoning process; the knowledge needed by a mentor; considerations about distance education, online teacher training and virtual learning environments. The research was based on a qualitative approach, based on an intervention research, with data analysis supported by the descriptive-interpretative methodology. The collected data come from the productions and activities carried out by the mentors regarding the monitoring of the beginning participants who completed the Online Mentors Education Program, featuring a documentary analysis; and answers to a questionnaire answered by the beginning teachers who agreed to answer it. The data were organized and then analyzed manually, looking for evidence that pointed to the training needs of the beginning teachers, mentoring actions carried out by the mentors and other information that contributed to the answers to the research questions. These data were classified in tables and frames. The results presented in this work indicate the profile of beginning teachers; the presence of the four categories of training needs - referring to students, referring to the curriculum, referring to the teacher and referring to the school as an organization - and how the mentors guided the PIs to assist them in overcoming or minimizing typical dilemmas. The analyzes show that, many times, the mentors chose to “give the fish”, instead of “teaching how to fish”, related metaphors that show the beginning teacher how to carry out the activities in teaching practice (“giving the fish”), or offering means, reflections and materials for the teacher to develop his skills (“teaching how to fish”). However, in most cases, the beginning teachers demonstrated that the mentoring process contributed positively to their professional development with practices and reflections that made the initial period less painful and lonely, offering alternatives to the characteristic feelings of this stage.
Online Mentors Education Program from UFSCar: contributions to the professional development of participating beginning teachers
Keywords: Programa de formação online de mentores; Professor iniciante; Necessidades formativas; Programa de mentoria; Mentor; Desenvolvimento profissional; Aprendizagem da docência; Online Mentor Education Program; Beginner teacher; Training needs; Mentoring program; Professional development; Teaching learning; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO